Reinstatement of Aloe davyana (Asphodelaceae subfam. Alooideae), a winter-flowering species endemic to central-northeastern South Africa - Smith, Gideon F.; Klopper, Ronell R.; Crouch, Neil R.; Figueiredo, Estrela (Phytotaxa, 2020)
Aloe davyana (Asphodelaceae subfam. Alooideae), a winter-flowering aloe that is endemic to the north-central interior of South Africa, is reinstated at the rank of species based on plant size, clumping habit, leaf colour and ornamentation, inflorescence architecture, and several flower characters. In the past it was sometimes treated as A. greatheadii var. davyana.